Optimization of alkali treatment condition on jute fabric for the development of rigid biocomposite. (January 2018) - Lakshmanan, Ammayappan; Ghosh, Rakesh Kumar; Dasgupta, Swati; Chakraborty, Sujay; Ganguly, Prasanta Kumar
Jute fiber has poor compatibility with hydrophobic thermosetting polymeric resin for the development of a biocomposite. In this present study, plain weave jute fabric was treated with 1% sodium hydroxide (owf) in three different time (30, 60 and 90 minutes), temperature (30, 40 and 50℃) and material-to-liquor ratio (1:5, 1:10 and 1:15) as per orthogonal array and the treated jute fabrics were used for the preparation of the biocomposite sheet by hand laying-cum-compression moulding method. Developed biocomposite sheets were evaluated for their mechanical properties as per ASTM standards and results were analyzed by Taguchi model to optimize the sodium hydroxide treatment condition. Results inferred that jute fabric reinforcement treated with 1% sodium hydroxide at 50℃ for 60 minutes in 1:10 material-to-liquor ratio could be the optimum condition to develop the biocomposite sheet with higher mechanical properties than other conditions.